2020
DOI: 10.1002/jia2.25439
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and other new media technology interventions for HIV care and prevention: a systematic review

Abstract: Introduction Electronic and other new media technologies (eHealth) can facilitate large‐scale dissemination of information and effective delivery of interventions for HIV care and prevention. There is a need to both monitor a rapidly changing pipeline of technology‐based care and prevention methods and to assess whether the interventions are appropriately diversified. We systematically review and critically appraise the research pipeline of eHealth interventions for HIV care and prevention, including published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 128 publications
0
60
0
8
Order By: Relevance
“…MSM and male sex workers are often mobile, which may impact LTFU [10,12]. Providing information about LGBTQ‐friendly PrEP‐providing facilities through peers or eHealth support [28], may improve continuity of care when participants move or decide to change clinics.…”
Section: Resultsmentioning
confidence: 99%
“…MSM and male sex workers are often mobile, which may impact LTFU [10,12]. Providing information about LGBTQ‐friendly PrEP‐providing facilities through peers or eHealth support [28], may improve continuity of care when participants move or decide to change clinics.…”
Section: Resultsmentioning
confidence: 99%
“…In Kenya, where same-sex behavior is stigmatized, PrEP-taking individuals may benefit from a peer support model, which recently led to improved ART adherence among MSM in a pilot study in coastal Kenya [36] . In addition, interventions such as eHealth technologies and intensified engagement are needed to support retention of MSM in PrEP care which may improve PrEP adherence over time [37] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors noted that few online interventions had occurred in low-and middle-income countries. Another study assessing the effectiveness of using Grindr to increase HIV self-testing among Black and Latino MSM in Los Angeles found online interventions resulted in more linkage to testing than offline outreach, and a greater likelihood to reach untested high-risk populations (Maloney, Bratcher, Wilkerson, & Sullivan, 2020). Yet, it was found that such interventions were also limited to individual behaviour change by only encouraging testing and education, resulting in an absence of interventions addressing linkage to and retention in care, or adherence.…”
Section: Discussionmentioning
confidence: 99%